OPERATION SIMULATION OF WIND POWER STATION WITH REGARD TO CONNECTION CONDITIONS OF DISTRIBUTION SYSTEM OPERATOR (Perner's Contacts, 2011)
The paper deals with utilization of wind energy as renewable resource of electric energy generated by wind power plants, their connectivity options and their operating within an electrical energy distribution network. The emphasis is laying particularly on resource influence in electrical energy distribution networks which will be evaluated using the E-vlivy program by EGC - EnerGoConsult ČB, s.r.o. The simulation outcomes are compared with manual calculation and the obtained measurements of electric energy quality parameters.
Keywords: wind; wind power plant; energetics; connection; resource influence